Dimension of Attitudes in Flipped Learning: Enjoyment, Engagement, Motivation, Behavioral Intention, and Perception - Oya, Abas; Parmiti, Desak Putu; Jampel, I Nyoman; Candiasa, I Made; Susilawati, Aay (Universitas Negeri Makassar, 2024)
This research investigates the influence of video-based flipped learning on the attitudes of students in non-English language programs, focusing on enjoyment, engagement, motivation, behavioral intentions, and perception. The study employed a descriptive research design, collecting data through questionnaires administered to 30 students enrolled in non-English language courses. The findings reveal a significantly positive attitude towards flipped learning, with high scores in enjoyment and engagement indicating a preference for the interactive and dynamic nature of video-based learning environments. The study confirms that motivation and behavioral intentions are positively affected by the flipped model, enhancing students' proactive learning behaviors and overall engagement with the course material. Moreover, the positive perception of video-based learning among students suggests that this method supports a deeper understanding and retention of language skills. This research contributes to the educational discourse by demonstrating that flipped learning models can significantly improve learning experiences and outcomes in non-English language settings. Future studies are encouraged to explore the long-term impacts of flipped learning on language proficiency and retention, aiming to validate and expand upon the current findings.